Assessment of periodontal health status in patients undergoing renal dialysis: A descriptive, cross-sectional study - Bhatsange, Anuradha (Medknow Publications & Media Pvt Ltd, 2012)
OBJECTIVE: An inter-relationship between periodontal disease and systemic health has been suspected for centuries, but evidence to explain the connection has only been elucidated in the past few decades. Among the systemic diseases, end stage renal disease has been shown to affect not only the general health of the patient but also oral and periodontal health. This study was undertaken to gain an insight into whether duration of dialysis therapy influences the oral and periodontal health of these patients and also to see if these parameters reflect their biochemical values. MATERIALS AND METHODS: The study was conducted on 75 patients undergoing dialysis and a control group of 25 subjects. The study group was divided into three subgroups depending upon the duration of dialysis. Oral hygiene and periodontal disease status were measured by Simplified Oral Hygiene Index by Greene and Vermillion and Periodontal Disease Index by Ram-fjord. Biochemical parameters measured were blood urea nitrogen and salivary urea levels. Comparison of these parameters was made between the study and control groups through analysis of variance (ANOVA) and student's t-test. RESULTS: Prevalence of periodontal disease was evident in the dialysis group. Oral hygiene status was poor in comparison with the control group. Clinical and biochemical parameters showed statistically significant difference between the groups rather than within the groups. CONCLUSION: Oral and periodontal health appeared to be compromised. Their deteriorating general health is anticipated to cause negligence towards oral health care. This population needs comprehensive oral and periodontal care right from the diagnosis of chronic renal failure. There exists a need for communication between nephrologists and oral health care professionals. Longitudinal studies warranted in this regard.